A Rare but Real Necessity: Case Report of Coronary Artery Stenting in an Infant - Martins, JD (2022)
Percutaneous coronary intervention (PCI) is an extremely common and well-established procedure in adults which is rarely performed in children. We present a case of a successful left main coronary artery stenting in a small infant with a congenital coronary artery anomaly. We highlight the technical challenges of performing a PCI in a small patient, the risks of antithrombotic prophylaxis in this age group, and the importance of the combined work of the adult and pediatric interventional cardiologist.